Vloga mikrocistinov pri razvoju bolezni parenhimskih organov - Repež, Andrej (Medicinski razgledi, 1998)
Microcystins damage liver tissue by disorganizing the cytoskeleton and inhibiting serine threonine protein phosphatases. Liver cells shrink and bloodpenetrates the liver tissue. Internal bleeding may lead to haemorrhagic shock. Water pollution associated with the blooming of toxic cianobacteria as a result of intensive agriculture has been well-documented in the north-eastern Slovenia. We undertook to develop a method for isolation of hepatocytes, and to assess the potency of microcystin RR isolated from the polluted water in Slovenia. By acute exposure of rats to a mixture of microcystins RR and LR we wanted to ascertain whether internal bleeding reflects changes in the haematocrit cound. Morphological changes following chronic exposure of animals to microcystin mixture were studied. Simultaneously, we tested the hypothesis that magnetic resonance (MR) imaging is a suitable technique for assessing acute and chronic toxicity of microcystins. The experiments were performed on 37 male Wistar rats. Twenty animals were sacrificed during acute experiments. The effects of the chosen toxin on the isolated hepatocytes obtained by in situ perfusion technique weretested in half the animals, while in another half the toxin in half the animals, while in another half the toxin mixture effects were assessed in vivousing MR imaging. For chronic tests the animals were fed with microcystinsfor two months. Blood was drawn from the inferior caval vein for complete blood count and serum analysis. The liver was removed and weighed andliver specimens were obtained for histological examination. The hepatocyte isolation method afforded a 83% cell survival.(Abstract truncated at 2000 characters)
Keywords: Liver; mikrocistini; Pathology; toksičnost; strupi; Bacterial toxins; Cyanobacteria; jetra; podgane; Pathogenicity; Water pollution; Magnetic resonance imaging; Histology, comparative; Rats, wistar; Blood chemical analysis; Cytoskeleton; Protein-serine-threonine kinases